TINDAK BAHASA TERAPIS DALAM INTERVENSI KLINIS PADA ANAK AUTIS - Luluk Sri Agus Prasetyoningsih (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe types, functions, and strategies of therapeutic languageacts in clinical interventions on autistic children. It employed the qualitative approachusing the clinical pragmatic design. The findings are as follows. First, clinical therapeuticinterventions on autistic children use illocutionary acts in the forms of directive, assertive,and expressive acts. In general, they use simple utterance patterns. Second, therapeuticverbal acts have functions to command, invite, require, refuse, ask, agree, state, explain,compliment, thank God, and thank. Third, strategies of therapeutic language acts are inthe form of direct utterance strategies by means of calling, giving directions, and usingvisual objects or models.